Vaccine-induced immune thrombotic thrombocytopenia in a male after Ad26.COV2.S vaccination presenting as cerebral venous sinus thrombosis. (4th July 2022) - Wu, James Fan; Bajwa, Umair; Hammad, Muhammad
Abstract: Vaccine-induced immune thrombotic thrombocytopenia (VITT) is a rare and life-threatening complication that can occur after COVID-19 vaccination. After the first reports of VITT and CVST in 2021 after Ad26.COV2.S vaccination, the FDA and CDC recommended an emergency pause on 13 April 2021, and after extensive safety reviews, on 23 April 2021, the CDC's Advisory Committee on Immunization Practices (ACIP) reaffirmed its original recommendation for use of the Ad26.COV2.S vaccination. As of 31 August 2021, in the United States, 54 cases of VITT following Ad26.COV2.S vaccination (37 female, 17 male) have been reported out of 14.1 million total shots given, 29 of which had cerebral venous sinus thrombosis (CVST). With more data, on 16 December 2021, the CDC endorsed the ACIP recommendations for individuals to receive an mRNA COVID-19 vaccine in preference over the Ad26.COV2.S vaccination. We report a rare case of a male with confirmed VITT and CVST following Ad26.COV2.S vaccination.